2015
DOI: 10.1088/2041-8205/810/2/l25
|View full text |Cite
|
Sign up to set email alerts
|

A Definition for Giant Planets Based on the Mass–density Relationship

Abstract: We present the mass-density relationship (log M -log ρ) for objects with masses ranging from planets (M ≈ 0.01 M Jup ) through stars (M > 0.08 M ). This relationship shows three distinct regions separated by a change in slope in log M -log ρ plane. In particular, objects with masses in the range 0.3 M Jup to 60 M Jup follow a tight linear relationship with no distinguishing feature to separate the low mass end (giant planets) from the high mass end (brown dwarfs). The distinction between giant planets and brow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 28 publications
8
113
0
Order By: Relevance
“…Since the mass and radius measurements for both planets are affected in the same way by the systematic uncertainties of the stellar parameters, the diversity of exoplanets (e.g., Hatzes & Rauer 2015) cannot be entirely explained by problems in the determination of the stellar parameters. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since the mass and radius measurements for both planets are affected in the same way by the systematic uncertainties of the stellar parameters, the diversity of exoplanets (e.g., Hatzes & Rauer 2015) cannot be entirely explained by problems in the determination of the stellar parameters. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This casts doubts on the proposed distinction between BDs and planets, which is thought to be connected to different formation mechanisms. Hatzes & Rauer (2015) proposed that objects in the mass range 0.3-62 M Jup follow the same relationship on the observed mass-density plot, so they should be considered to belong to one and the same class of celestial objects. Based on planet population synthesis, Mordasini et al (2009) showed that the core-accretion mechanism proposed for giant planet formation may produce planets not only more massive than 13M Jup , i.e., above the deuterium burning limit (Burrows et al 2001), but also in the 20-40M Jup range.…”
Section: The Sample Of Brown Dwarfs Transiting Main Sequence Starsmentioning
confidence: 99%
“…Radial velocity measurements are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/608/A129 around 2 R Jup (Sato et al 2005;Anderson et al 2010), a range in size which also corresponds to late M dwarfs with masses lower than ∼0.2 M (Chabrier & Baraffe 1997;Baraffe et al 1998Baraffe et al , 2015Dotter et al 2008;Demory et al 2009;Díaz et al 2014;Hatzes & Rauer 2015;Chen & Kipping 2017). To further the comparison, gas giants, brown dwarfs, and very low-mass stars also have similar temperatures in addition to similar sizes.…”
Section: Introductionmentioning
confidence: 99%